Effect of long-term treatment with steroid hormones or tamoxifen on the progesterone receptor and androgen receptor in the endometrium of ovariectomized cynomolgus macaques - Cline J Mark; von Schoultz Bo; Isaksson Erika; Wang Hong; Sahlin Lena (Reproductive Biology and Endocrinology, 2003)
Abstract The progesterone receptor (PR) and androgen receptor (AR) belong to the nuclear receptor superfamily. Two isoforms of PR (A and B) have been identified with different functions. The expression of AR, each isoform of PR and their involvement in long-term effects on the endometrium after hormonal replacement therapy (HRT) or tamoxifen (TAM) treatment is not known. The aims of this study were to determine PR(A+B), PRB and AR distribution by immunohistochemistry in the macaque (Macaca fascicularis) endometrium. Ovariectomized (OVX) animals were orally treated continuously for 35 months with either conjugated equine estrogens (CEE); medroxyprogesterone acetate (MPA); the combination of CEE/MPA; or TAM. Treatment with CEE/MPA tended to down-regulate PR in the superficial glands, but increased it in the stroma. TAM treatment increased both the PR and PRB levels in the stroma. Overall, less than 20% of the cells were positive for the PRB isoform and less variation was observed after steroid treatment. AR was found in the stroma, mainly distributed in the basal layer of the endometrium in the OVX and steroid treated groups, but was absent in the TAM treated group. No AR was found in the glandular epithelium. The present data show that long-term hormone treatment affects the PR level, and also the ratio between PRA and PRB in the endometrium.